Multicatheter interstitial brachytherapy for breast cancer - Sumodhee, S.; Strnad, Vratislav; Hannoun-Levi, J. -M. (Cancer Radiotherapie, 2018)
Brachytherapy remains the best irradiation technique to deliver a high dose in a small volume. Breast brachytherapy is part of the arsenal of therapy in the management of breast cancer. In this article, we present the technical data related to multicatheter interstitial brachytherapy to the breast proceeding, from the implantation of the vectors to the treatment itself. The indications for brachytherapy in breast cancer are boost after whole breast irradiation, accelerated partial breast irradiation or selected patients with second ipsilateral breast tumor event. The results in terms of efficacy and toxicity are presented for each indication. Multicatheter interstitial breast brachytherapy remains a major technique for breast cancer treatment.
EVALuna2:36540